Синяя кровь: роман / Ю. В. Буйда - Буйда Юрий Васильевич (Эксмо, 2011)
Экземпляры: АБ (20120903) / Инвентарный номер: 41094zzzzz / Цена: 440.59 / Сис.шифр: 84(2) / Авт.знак: Б 90 / ГРНТИ: 17.82.31 / ББК: 84(2=Рус)